1992
DOI: 10.1152/ajprenal.1992.262.1.f117
|View full text |Cite
|
Sign up to set email alerts
|

Taurine attenuates renal disease in chronic puromycin aminonucleoside nephropathy

Abstract: Repeated administration of low doses of puromycin aminonucleoside (PAMN) to rats induces a proteinuric renal disease that resembles focal segmental glomerulosclerosis (FSGS). Reactive oxygen molecules may be involved in the progressive course of this nephropathy. Therefore we evaluated whether taurine, an endogenous antioxidant, could limit the extent of renal injury. Sprague-Dawley rats received low-dose injections of PAMN, 2 mg/100 g body wt, over a 12-wk period. Two groups were studied: 1) controls given ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 13 publications
1
37
1
Order By: Relevance
“…Pre-incubation of hepatocytes with taurine could significantly decrease ROS formation. Taurine is an amino acid with a sulfonic acid group, and probably reacts with reactive oxygen species;complex formation between sulfonic acid group (SO3 -) to free ion species has been reported (Trachtman et al, 1992). Hence, the reactive oxygen species formed during carbamazepine metabolism were scavenged by taurine, this may have had a role in its protective effects in carbamazepine cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-incubation of hepatocytes with taurine could significantly decrease ROS formation. Taurine is an amino acid with a sulfonic acid group, and probably reacts with reactive oxygen species;complex formation between sulfonic acid group (SO3 -) to free ion species has been reported (Trachtman et al, 1992). Hence, the reactive oxygen species formed during carbamazepine metabolism were scavenged by taurine, this may have had a role in its protective effects in carbamazepine cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid as a scavenger may play a role as an antioxidizing agent in plasma by maintaining Fe2+ in the reduced state (18,19). It has also been suggested that the sulfonic acid group of taurine could bind or complex to free metal ion species (Fe2+, Cu2+) or to oxidant metalloproteins, and react with by-products of oxidation reactions, thereby preventing a direct attack by oxidants on cell membranes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oxidative stress leads to progression of glomerulonephritis by producing nicotinamide adenine dinucleotide phosphate oxidase [20,21]. NAC has considerable effects on free radicals and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that taurine protects renal tissues against damage from oxidative stress [18][19][20][21]. To further investigate, we studied the therapeutic efficacy of NAC and taurine in proteinuria in DN.…”
Section: Introductionmentioning
confidence: 99%